Keanekaragaman Serangga Polinator Pada Tanaman Nanas (Ananas comosus (L.) Merr.) Di Desa Bincau - Trianto, Manap; Kaini, Kaini; Saliyem, Saliyem; Warsih, Eko; Winarsih, Winarsih (Biosel Biology Science and Education, 2020)
Pollinator insects is an animal that moves pollen from the male anther of a flower to the female stigma of a flower. The purpose of this study was to determine the diversity of insects pollinators in the pineapple (Ananas comosus (L.) Merr.) plantation of Bincau Village, Martapura District, Banjar Regency, South Kalimantan. Sampling was done by purposive sampling using a yellow sticky trap. The customer observations are made in visual control. Observation starts at 07.00-18.00 WITA which is divided into 3 time periods, namely: 07.00-10.00 WITA, 11.00-14.00 WITA and 15.00-18.00 WITA. The data obtained were analyzed using the diversity index Shannon-Wiener (H'). The results showed that the total individual of pollinator insects in pineapple plantations was 517 individuals, consisting of 4 order and 8 family. The highest abundance of insects is dominated by the Formicidae Family, while the lowest abundance is the Syrpidae Family. Value insect pollinator diversity found among the sites that H' = 1.760 which indicates that the level of diversity of insect pollinators on plantations Pineapple (Ananas comosus (L.) Merr.) in the Bincau Village, Martapura District, Banjar Region, South Kalimantan in the medium category. Keywords: Diversity, Pollinator Insects, Pineapple, Bincau District